Gendered Subaltern in Abhi Subedi’s Dreams of Peach Blossoms - Niraula, Sanjeev (Contemporary Research: An Interdisciplinary Academic Journal, 2021)
This paper examines the consciousness of gendered subaltern in Abhi Subedi’s poetic play Dreams of Peach Blossoms and looks at how Subedi deconstructs the existing historiography to bring forth the issue of gendered subaltern who have been subjected to the hegemony of the ruling class. Drawing on insights and postulations from Subaltern Studies theorists such as Gayatri Chakravorty Spivak, Partha Chatterjee, Gautam Bhadra and others, this paper examines the pain and agonies of female characters that are glossed over in the grand narrative of the mainstream culture. This paper concludes that while exploring the painful experience of women erased from the pages of history, Subedi is focused on the Maiju culture that began since Bhrikuti’s marriage to a Tibetan King in the sixth century and reveals the injustice of patriarchy against women with an aim to make correction in such distortions of history.